Advances in Alignment Based Optically Pumped Magnetometers: Techniques, Characterisation and Applications - Elson, Lucy Jade (2025)
Eddy current induction in objects is a technique that can be used for detection, characterisation and imaging of a sample. By using a primary radio frequency magnetic field eddy currents can be induced in an object which in turn produces a secondary magnetic field. This secondary magnetic field can then be measured using a magnetic field sensor such as a fluxgate magnetometer or an optically pumped magnetometer (OPM). The characteristics of the magnetic field sensor chosen need to be considered in order to ensure the noise floor, operational frequency and band width are sufficient. In this thesis, experiments and numerical simulations for the evaluation of conductive objects are carried out. A commercially available fluxgate magnetometer is used to detect and characterise a non-magnetic (aluminium) and magnetic (steel) sample. The frequency dependence (up to 1 kHz) and positional dependence of the secondary magnetic field is investigated.